Analysis of Employee Work Environment at PT. Sinar Galesong Mandiri Aroepala Branch in Makassar City - Ipahriani Rahman; Muhammad Darwis; Sulmiah Sulmiah (Public Resource Innovation Management and Excellence, 2026)
This study aims to find out how the work environment of employees at PT.Sinar Galesong Mandiri Aroepala Branch in Makassar City. This study uses a qualitative method with a descriptive research type. Data collection techniques used in the form of observation, interviews and documentation. As for checking the validity of the data is done through credibility (degree of trust), transferability (transferability), dependability (dependence) and confirmability (certainty). Data analysis techniques use data collection, data condensation, data presentation and drawing conclusions. The results showed that the work environment of employees at PT.Sinar Galesong Mandiri Aroepala branch in Makassar city was inadequate, as the physical work environment still had several deficiencies which included workplace buildings, work equipment, rest areas and places of worship. This needs to be considered by the company in improving employee performance. While the non-physical work environment is very good. The reason is because in the work environment, employees still maintain good relationships with other employees, superiors always supervise their subordinates, and cooperation between employees is always implemented.